Affixation Process of Minangkabaunese in Nagari Pamuatan Sijunjung Regency - Dewi Nengsih, Arfina (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2019)
The purpose of this research was to describe affixation process of Minangkabaunese in Nagari Pamuatan. The Data was gotten from daily conversation of native speakers in Nagari Pamuatan, Kupitan district, Sijunjung regency. The method used in this research was observational method through recording, interview and taking field notes technique. The data was analyzed by using translational equal method through dividing key factors technique. Then, it also uses distributional method through segmenting immediate constituent’s technique. The Result of this research shows that there are some affixation forms namely prefix, suffix, circumfix, simulfix, and compound of affixes. Some of them seem to have uncommon affix form as found in minangkabaunese. For example, prefix ba- which belongs to allomorph bǝ-, prefix ta- which belongs to allomorph prefixes tǝ- and prefix sa- which belongs to allomorph prefiks sǝ-